“Futurology” and Higher Education in the Post-COVID-19 Environment - Locke, William (International Higher Education, 2021)
Even before COVID-19, futurologists maintained that a number of disruptions to higher education were combining to create cataclysmic scenarios for universities. These claims inform an increasingly dominant policy and management discourse about the need for rapid and radical transformations in academic conventions, business models, and working practices. However, what is needed are evidence-based and iterative approaches to imagining the future, drawing on universities’ own experiments with new forms of higher education.